Microbial Ecology in the Age of Omics: Exploring Microbe-Environment Interactions - Obyes, Muhammad Khudair; Juma, Heba Ahmed; Hassan, Tebai Abbas; Hassan, Munir Falah; Zuwaid, Abdul Khaleq Muhammad (American Journal of Biology and Natural Sciences, 2025)
Microbial ecology has undergone a paradigm shift with the emergence of omics technologies, offering unprecedented insights into microbe-environment interactions. Despite major advancements, challenges remain in integrating multi-omics data to fully understand microbial community structure, function, and dynamics within complex ecosystems. This review highlights recent progress in genomics, metagenomics, transcriptomics, proteomics, and metabolomics, and their combined application to study microbial communities. Findings show that microorganisms are essential drivers of biogeochemical cycles, host-microbe interactions, and ecosystem resilience, with omics-based methods uncovering previously unknown microbial diversity and metabolic capabilities. However, the complexity of data analysis, limited culturing of environmental microbes, and incomplete understanding of microbial functional roles persist as key barriers. The results emphasize the necessity for interdisciplinary approaches, improved bioinformatics tools, and systems biology integration to achieve a predictive understanding of microbial ecosystems and their role in global environmental and health-related processes.